INTERACTION PATTERN BETWEEN FISHERS AND FOREIGN INVESTORS IN THE FISHING BUSINESS AND ITS IMPLICATIONS (A CASE IN NUNUKAN REGENCY, EAST KALIMANTAN) - Iin Solihin; Sugeng Hari Wisudo; John Haluan; Drajat Martianto (Research Center for Fisheries, 2012)
The objective of this research is to determine patterns of interaction between fishers and foreign investors (Malaysia) in the fishing business. Research conducted on May 2009 in the Nunukan, East Kalimantan. The data retrieval was conducted by in depth interviews (deep interviews) with the fishersand middlemen as well as direct observations on the condition of the fishing business and marketing in both the Nunukan District and in Tawau Malaysia. The results showed that there is a relatively large dependence of the fishers in Nunukan District to the owners of capital from Tawau regarding capital provision, marketing of the catch, and social security.